Study on the substantiation of location equilibrium in the CUE model - Hiromichi Yamamoto; Atsushi Koike; Hajime Seya (Journal of Urban Management, 2019)
In the Computable Urban Economic (CUE) Model, one land-use transport interaction (LUTI) model, improving the accuracy of the Location Choice Model is important to evaluate the effects of introducing urban transportation policies. However, our previous study revealed that the substantiation of the indirect utility function by a linear expenditure system has not been verified and that location choice behaviors estimated using the logit model depends on the adjustment factor. Therefore, in this study, we first examined the logical meaning of the utility function by a linear expenditure system, and then focused on identifying major constituent factors of the adjustment factor and statistically verified the adjustment factor and urban amenities. As a result, we have identified the following facts: that the conventional indirect utility function may underestimate the effect of introducing urban transportation policies; that if effects are estimated using WLS after adding housing supply factors to the indirect utility function, the estimation accuracy will be improved; and that the major constituent factors of the adjustment factor are those expressing local characteristics of cities and wards.
Keywords: 710; CUE Model; Logit model; LUTI Model; Residential location choice model; Transport economics